한국 자포니카 품종에서 벼퉁그로 바이러스병 저항성 탐색 - 이종희(Jong Hee Lee):조준현(Jun-Hyeon Cho):이지윤(Ji-Yoon Lee):강주원(Ju-Won Kang):신동진(Dongjin Shin):조수민(Sumin Jo):최일룡(Il-Ryong Choi):송유천(You-Chun Song):박동수(Dong-Soo Park); 고종민(Jong-Min Ko) (Korean journal of breeding, 2019)
Rice tungro disease is a serious threat to rice production in South and Southeast Asian countries. Rice production in these countries has been intensified, often through continuous cultivation of rice. We conducted a screen of the resistance to tungro virus disease in Korean japonica rice. Dongjin, Hwaseong, and Sangju were varieties resistant to Rice tungro spherical virus (RTSV) but susceptible to Rice tungro bacilliform virus (RTBV). RTSV-resistant variety Sangju was crossed with RTSV-susceptible variety Unkwang to conduct a genetic analysis for RTSV resistance originating from Sangju. Evaluation of 201 F2 plants from the cross between Unkwang and Sangju showed that there were 85 plants showing resistance, and that 116 plants were susceptible, indicating a ratio fitting a 7:9 ratio ratio (χ2 = 0.54; p = 0.46). Thus, the resistance to RTSV in Sangju might be controlled by two recessive genes. This result indicates that Sangju might serve as a useful genetic source for diversification of RTSV resistance and stabilization of resistance through gene pyramiding. KCI Citation Count: 1